2009
DOI: 10.1080/08905430802671956
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Nine Bacteriocins Produced by Lactic Acid Bacteria Isolated from Cold-Smoked Salmon with Activity againstListeria monocytogenes

Abstract: Nine LAB bacteriocin-producers, isolated from vacuum-packaged cold-smoked salmon (CSS), were phenotypically and genotypically identified as Lactobacillus curvatus, Lactobacillus delbrueckii, Lactobacillus fermentum, Enterococcus faecium, and Pediococcus acidilactici. Their bacteriocins were partially characterized. The antimicrobial spectrum was determined against Listeria monocytogenes, E. faecalis, E. faecium, and Staphylococcus aureus. The molecular size of bacteriocins ranged from 2.8 to 4.5 kDa. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Thus, the bacteriocin preparation was stable at acidic and neutral pH but unstable at alkaline pH, which was also observed in an earlier report (Tome et al . ). The bacteriocin retained its activity up to 100C, but complete loss of activity was observed at 121C indicating it was heat stable and not autoclavable (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the bacteriocin preparation was stable at acidic and neutral pH but unstable at alkaline pH, which was also observed in an earlier report (Tome et al . ). The bacteriocin retained its activity up to 100C, but complete loss of activity was observed at 121C indicating it was heat stable and not autoclavable (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…The activity of the cell‐free supernatants of the studied strains against most of the tested L. monocytogenes strains (Table 1) is quite interesting, particularly because many reports have shown that L. monocytogenes is an important foodborne pathogen, present in several foods, including fresh trout samples and smoked salmon (Hangard‐Vidaud et al. 1989; Tomé et al. 2008, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…acidilactici ET34 and Ent. faecium ET05, ET12 and ET88 were isolated from smoked salmon (Tomé et al. 2009) obtained from same production plant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They should grow during temperature abuse, either producing acid or bacteriocins, or make the product inedible, which would warn the consumer of a hazard (Juneja 2006). This approach has been investigated for cold-smoked salmon by using lactic acid bacteria (LAB) (Tome et al 2008(Tome et al , 2009). Among heat-processed products, little information is available for the addition of LAB on seafood, but pork has been investigated (Laursen et al 2009).…”
Section: Combination Effectsmentioning
confidence: 99%